Menentukan Jumlah Pasokan Komoditas Pangan di Provinsi Riau Berdasarkan Fuzzy Inference System dengan Metode Fuzzy Tsukamoto - rahmawati ama rahmawati (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2018)
Food is the primary need of the population in Indonesia. Increased food demand along with the increasing of population growth. Food availability is an aspect to be met by the Indonesia government as an effort to prosper the community. In facts, food availability in a country or a region not always can be met well. Therefore, the government needs to stabilize the level of food availability, one of the efforts is by importing or supplying food from abroad. Food supply planning needs to be done carefully so as not to shut down domestic food production and it was expected to stabilize food security. Planning of the quantity of food commodity supply  will be done by taking into account the number of population needs and the number of food production itself. Because the number of food needs and production is very relative and always changing at a certain time, then to determined the amount of food supply will be done with fuzzy inference system. Tsukamoto’s fuzzy method is one of the methods in the fuzzy inference system. So, the result of this research is to find of food commodity supply in Riau Province based on number of food need and number of food production with fuzzy inference system using Tsukamoto's fuzzy method.